Nanoparticle-Embedded GelMA/NIPAm Hydrogels: A Temperature-Responsive Hybrid System for Controlled Drug Release - Daaboul, Maria; Akkaya, Ayse; Kanli, Zehra; Gunduz, Oguzhan; Aydin, Banu; Alarcin, Emine; Ozmen, Mehmet Murat; Topuzogullari, Murat (WILEY-V C H VERLAG GMBH, 2026)
Temperature-responsive hydrogels incorporating drug-loaded polymeric nanoparticles represent a significant advancement in controlled release systems, enabling responsive and environmentally triggered drug delivery. In this study, a novel temperature-responsive drug delivery system was developed based on a gelatin methacryloyl/N-isopropylacrylamide (GelMA/NIPAm) hydrogel incorporating phenytoin (PHT)-loaded poly(D,L-lactide-co-glycolide) (PLGA) nanoparticles. For this, empty nanoparticles, PHT-loaded nanoparticles, bare hydrogels (BH), empty nanoparticle-loaded hydrogels (eNP-H), and PHT-encapsulated nanoparticle-embedded hydrogels (PHT-H) were prepared and characterized using FTIR, SEM, DSC, XRD, DLS, swelling, drug release, and biocompatibility tests. The drug-loaded nanoparticles exhibited hydrodynamic diameter of 223.7 +/- 8.4 nm with a PDI of 0.298 and a zeta potential of -20.4 mV. The BH, eNP-H, and PHT-H hydrogels displayed similar temperature-dependent swelling, with approximate weight swelling ratios of 9.0 at 25 degrees C, 7.5 at 37 degrees C, and 6.0 at 40 degrees C. Swelling kinetics showed that all hydrogels reached equilibrium within 20 min. Moreover, the hydrogels demonstrated consistent cyclic swelling and shrinking at 37 degrees C and 40 degrees C. Drug release studies revealed that PHT-H hydrogels released similar to 20% of phenytoin at 37 degrees C and similar to 34% at 40 degrees C over 7 days, confirming sustained, temperature-responsive drug release. Cell viability assays indicated no cytotoxicity and potential promotion of cell proliferation. Thus, these hydrogels offer a promising platform for efficient, temperature-sensitive, and controlled drug delivery applications.
Keywords: drug delivery; hydrogel; nanoparticle; PLGA; temperature-responsive; GRAPHENE OXIDE; GELMA/PEGDA; Biochemistry & Molecular Biology; Materials Science; Polymer Science